Evaluation of the biological activities of Copaiba (Copaifera spp): a comprehensive review based on scientometric analysis - Frazão, Deborah Ribeiro; Cruz, Jorddy Neves; Santana de Oliveira, Mozaniel; Baia-da-Silva, Daiane Claydes; Nazário, Rayssa Maitê Farias; Rodrigues, Matheus Ferreira de Lima; Saito, Miki Taketomi; Souza-Rodrigues, Renata Duarte; Lima, Rafael Rodrigues (Frontiers in Pharmacology, 2023)
Copaíba oil-resin is extracted from the trunk of the Copaíba tree and has medicinal, cosmetic, and industrial properties. As a result, widespread knowledge about the use of Copaíba oil-resin has evolved, attracting the scientific community's attention. This paper aims to map the global knowledge production regarding the biological activities of Copaíba (Copaifera spp.). Bibliometric methodological instruments were used to conduct a search of the Web of Science-Core Collection database. The search resulted in 822 references. After screening titles and abstracts, 581 references did not meet the eligibility criteria, leaving 246 references for full-text examination. Subsequently, 15 studies were excluded, resulting in a final set of 232 records for the bibliometric analysis. In vitro was the most published study type, mainly from Brazil, from 2010 to 2020. Regarding the authors, Bastos, JK, and Ambrosio, SR were the ones with the most significant number of papers included. The most frequent keywords were Copaíba oil, Copaíba, and Copaifera. Our findings revealed global study trends about Copaíba, mainly related to its various effects and use over time. In general, all countries have conducted more research on antimicrobial and anti-inflammatory activities, also exposing its antioxidant and healing properties. Copaifera reticulata was the most investigated, followed by Copaifera langsdorffi and Copaifera multijuga in both in vitro and in vivo studies. Therefore, there is a need for human reports, given the promising results that Copaíba oils have been demonstrating.